Forged in desire - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Protectors., 2017)
When good girl Margo Connelly becomes bodyguard Lamar "Striker" Jennings' latest assignment, she begins to wonder if the temptation of her alluring protector is more dangerous than the gangster targeting her.